2018
DOI: 10.3390/su10061882
|View full text |Cite
|
Sign up to set email alerts
|

E-Government Maturity Model for Sustainable E-Government Services from the Perspective of Developing Countries

Abstract: Electric government (e-government) projects in developing countries are facing many challenges to deliver sustainable e-government services. From the existing literature, we found that most of the studies considered lack of technology, and limitations in budgets and human resources as the main hurdles in effective implementation of e-government services. Along with these limitations, we found that the e-government maturity models adopted by developing countries are failing to provide an appropriate strategic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 26 publications
(47 reference statements)
1
52
0
7
Order By: Relevance
“…The case study approach is appropriate for this research as it provides the means to describe in detail the organizational dynamics of a phenomenon; in particular, it helps us to understand and explain how the dynamics and interactions among stages and factors of ICT implementation occur [10,12,[36][37][38][39]. Moreover, the authors prefer this approach since the modifications in this study's suggested ICT implementation model takes into account contemporary and near-future uncertainties that only the most technologically-advanced and leading organizations may have yet considered or experienced.…”
Section: Methods: Case Study Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The case study approach is appropriate for this research as it provides the means to describe in detail the organizational dynamics of a phenomenon; in particular, it helps us to understand and explain how the dynamics and interactions among stages and factors of ICT implementation occur [10,12,[36][37][38][39]. Moreover, the authors prefer this approach since the modifications in this study's suggested ICT implementation model takes into account contemporary and near-future uncertainties that only the most technologically-advanced and leading organizations may have yet considered or experienced.…”
Section: Methods: Case Study Approachmentioning
confidence: 99%
“…While these models are used to explain the different stages of e-government implementation by identifying characteristics that are specific to this technology and the public sector, more recent studies have further developed this framework by introducing the concept of sustainability. Joshi and Islam suggested a new e-government maturity model for promoting sustainable e-government services in developing countries [12]. Developing countries experience difficulties in implementing and providing e-government services to the public (e.g., limitations in technology, finance, and human resources).…”
Section: E-government Implementation and Public Engagementmentioning
confidence: 99%
“…Создание информационной среды для цифровизации государственного управления, как одной из ключевых целей деятельности государственных структур, основано на сложившихся методологических и научно-теоретических подходах к оценке содержания и трендах развития информационно-коммуникационных технологий в современных обществах (Napitupulu et al, 2017). В качестве базиса научных исследований информационнокоммуникационных технологий выступают обобщенные теории.…”
Section: методология (теоретические основы) исследованияunclassified
“…Необходимость использования информационно-коммуникационных технологий в сфере государственного управления объясняется концепцией «электронного правительства», или «электронного государства» (Бондаренко, 2012;Joshi et al, 2018).…”
Section: методология (теоретические основы) исследованияunclassified
“…The second one is for organizations that aim to progress to the intermediate maturity level (Level 3). Moreover, in the third Kit are the guidelines regarding the implementation of processes associated with the improved ICT maturity level (Levels 4-5), according to the maturity model proposed by Capability Maturity Model Integration (CMMI) [8,9]. This paper presents an account of the execution of a pilot project carried out at Brazilian Guarantees and Fund Management Agency (ABGF) State Company.…”
mentioning
confidence: 99%